(untitled) (Architecture Image Studies, 2020)
This article’s title follows a realization, in practice, of the tendency of eye-dominance in vision. The realization comes through a process of drawing in-situ around Hoamji Lake in Chungu, South Korea, written commentary on the drawings themselves as part of the in-situ experience, and more analytical reflection after the event. The process was repeated on the basis that experience would thereby accrue and deepen. The experiential component of the drawings, made in response to the question of how drawing on site, can inform how one thinks about place and space and how this adds authenticity to the visualization of place. – In this revision of an earlier published article, there is some reference to the author’s present involvement in architecture in an educational capacity –. The drawings, despite their landscape reference, are relevant in their attempt to capture movement and in their process to a prospective studio project with architecture students. Written reflection on the drawings concerns the interrelationship of drawing from observable phenomena and visual sensory perception. The activity itself, of drawing, enables the latter’s consideration, and such a focus in turn informs how the drawings are made, appear, and comment on the in-situ location. The article’s theoretical markers concern aspects of sensory cognition and phenomenological theory, particularly in the context of articulation of space.